Proposed upgrading of Zoo Taiping Restaurant for Zoo Taiping at Jalan Taman Tasik Taiping, 34000 Taiping Perak. / Siti Nurfarhanah Mansor Adby - Mansor Adby, Siti Nurfarhanah (Faculty of Architecture, Planning and Surveying, 2011)
This project title is Upgrading works of Zoo Taiping Restaurant for Zoo Taiping at Jalan Taman Tasik Taiping, 34000 Taiping Perak. Zoo Taiping was the client for this project and the director of this zoo is Dr. Kevin Lazarus. The existing Zoo Bistro Cafe does not have a welcoming environment which can attract visitor and because of that, the client want to upgrade the Cafe to a new image that can attract all kind of ages and at the same time include the wildlife nature ambiance into the cafe. This will be the first Zoo that has its own Theme cafe that related with the Zoo ambiance. To do the project, research and some interview need to be done to complete the requirement of the project. Site visit and building analysis has to be done in order to understand more about the building and the environment. The main objective is to provide a new image for the cafe and rearrange the space so the customer will more attracted to come and the services could run smoothly.